Economic sanctions: violation of human rights and the obligation to settle disputes peacefully - Popesku, Anna Marija (Riga Graduate School of Law, 2023)
The thesis examines the complexities surrounding economic sanctions, the violation of human rights, and the international obligation to settle disputes peacefully. The author explores controversies between the efficacy of economic sanctions as a tool of foreign policy and their potential negative impact on fundamental human rights. The research combines the legal analysis, case studies, as well as relevant international legal instruments to explore the legal and ethical implications of economic sanctions. Furthermore, it addresses the potential human rights violations resulting from economic sanctions, which tend to inflict a disproportionate suffering on the most vulnerable in a target state. These coercive measures tend to restrict access to basic necessities – food, water, and healthcare, thus violating fundamental human rights. Moreover, the thesis analyzes the obligation to settle disputes peacefully under international law.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Economic sanctions; Human rights; obligation to settle disputes peacefully